2013
DOI: 10.11634/21679606170646
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management and Financial Reporting Fraud: Can External Auditors Spot the Difference?

Abstract: The aim of this paper is to increase external auditors’ knowledge about earnings management and help them spot the difference between earnings management and financial reporting fraud. A thorough literature review was undertaken to achieve the paper’s aim. The secondary data used in this paper was obtained from different databases like Ebscohost, Business Search Premier, Academic Search Premier, Emerlad, Sciencedirect, and Jstor. The current paper suggests a new approach and way of thinking for external audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
1
18
0
5
Order By: Relevance
“…They continue to argue that among other reasons, which motivate managers to manipulate the company's earning is the use of accounting data toward monitoring and regulating the contract between the firms and stakeholders. Additionally, managers are opportunistically managing the real earnings to achieve their personal interest (Gul, Chen & Tsui, 2003;Kassem, 2012;Rahman, Moniruzzaman, & Sharif, 2013) and maintaining status of their stock process in the capital market (Rahman, et, al., 2013). This study is primarily conducted to examine the effect of board size, board composition and dividend policy on the real earning management in the Jordanian listed industries.…”
mentioning
confidence: 99%
“…They continue to argue that among other reasons, which motivate managers to manipulate the company's earning is the use of accounting data toward monitoring and regulating the contract between the firms and stakeholders. Additionally, managers are opportunistically managing the real earnings to achieve their personal interest (Gul, Chen & Tsui, 2003;Kassem, 2012;Rahman, Moniruzzaman, & Sharif, 2013) and maintaining status of their stock process in the capital market (Rahman, et, al., 2013). This study is primarily conducted to examine the effect of board size, board composition and dividend policy on the real earning management in the Jordanian listed industries.…”
mentioning
confidence: 99%
“…A similar research on tax reporting issues was done by (Kassem, 2012), who reported that there is a significant association between tax reporting and the investors' decision. He also argued that high levels of aggressive tax reporting could lead to accounting manipulation.…”
Section: Issues Of the Studymentioning
confidence: 62%
“…And not using a measurement were made to further investigate the link between the governance and the creative accounting. Kassem (2012) efforts to supply a uniqueness between fraud and creative accounting and reoffered to as an earnings management. Fraud is a material false statement whose target is to deceive and persuade reliance on the false statement by the victim.…”
Section: Literature Reviewmentioning
confidence: 99%